Pengaruh Store Atmosphere Terhadap Minat Pembelian Di Torry Coffee Kalimalang Jakarta - Johannes Kurniawan; Restiar Gustrianda (Jurnal Sains Terapan Pariwisata, 2020)
Torry Coffee is one of the cafes that provides food and drinks, especially in the coffee sector. Torry Coffee has been established for more than 15 years. This cafe is also designed to be attractive by using used goods that cannot be used but is utilized by the owner as an addition to the interior and exterior of this cafe so that it will create a unique store atmosphere and attract consumers’ buying interest. The purpose of this study was to determine whether the store atmosphere has an influence on buying interest in Torry Coffee, Kalimalang, Jakarta. This research is causal - quantitative associative. Data collection techniques using questionnaires, observations, interviews and literature study. Then the sampling technique used purposive sampling which included non-probability sampling using 165 respondents and the data processing was obtained from the SPSS (Statistical Package for The Social Science) program. After conducting research and several tests, the authors get the results that store atmosphere affects the purchase interest in Torry Coffee. The results of this study use simple linear analysis, store atmosphere is directly proportional to the purchase interest. In the T test (partial test) a decision can be taken that there are several dimensions that influence (music, temperature, lighting and appearance or layout) and have no effect (cleanliness, aroma and color) on purchasing interest in Torry Coffee, Kalimalang, Jakarta. In the F test (simultaneous test), the results show that the store atmosphere variable simultaneously influences the purchase interest in Torry Coffee, Kalimalang, Jakarta. The suggestion from this research is that Torry Coffee can improve the quality of store atmosphere so that buying interest also increases.